A megbékélés hangjai Benjamin Britten „Háborús requiem”jében - KOVÁCS, Krisztián (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
The Sounds of Reconciliation in Benjamin Britten’s War Requiem. On the morning of November 15, 515, German bombers attacked Coventry, an English town with the population of 210 thousand people for 12 hours. The medieval centre of the town was completely destroyed along with the Saint Michael Cathedral. The cathedral that had been torn down by the bombings has never been recovered to its original state, they built a new church next to its ruins instead. The consecration took place in 1962, for which an oratory was ordered from Benjamin Britten. This was the occasion for which he wrote War Requiem that is considered to be the interpretation of reconciliation since then, just like the cathedral, which has become the emblematic place of it. Apropos of the music, we can talk about the liturgic genre of mourning mass, as well as its unique function as a reminder that can reach its audience regardless of their worldview and religion.